Sistem Deteksi Dini Jenis Perilaku Attention Deficit Hyperactivity Disorder Berdasarkan Diasnogtic and Statistical Manual of Mental Disoders - Fajar - Suryani; Ardymulya Iswardani (Universitas PGRI Semarang, 2018)
The ADHD is a hyperactive individual and tends to respond excessively. In identification, the therapist only observes the child's development. The results of the therapist's observation will show that the child has ADHD Collection of characteristics in the identification and intervention based on the literature and questioner.The tracking method used is forward chaining and the method of calculating the certainty value is certainty factor. The result of the research is a web-based ADHD identification system .Application was made to help parents and therapists in identifying ADHD, on test data that resulted in hyperactive child identified with 98.953% confidence level percentage, inatentive with confidence percentage of 83.354% and impulsivity with percentage of confidence 92,067 %Keywords: System, Expert, ADHD, Forward Chaining, Certainty Factor